(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
A reduced-scale M4 wave energy converter was deployed in King George Sound off Albany, Western Australia, on 8 November 2024, marking its first test in a real sea environment. The M4 is a floating self-reacting hinged attenuator with multiple floats. The version deployed in Albany consists of a triangular front structure with three floats and a back arm with one float, and measures 24 m in length and 9.5 m in width. Station keeping is achieved through a single-point mooring system with a mooring buoy, catenary and ground lines, clump weights, and anchors. The device is instrumented with motion sensors, encoders, and load shackles, enabling measurement of motion in seven degrees of freedom (DOF) and mooring loads. A nearby wave buoy collects wave data, while wind data is available from an anemometer in the Sound. This paper presents preliminary findings, including the device’s weathervaning behaviour, motion responses, and mooring loads. Measured response amplitude operators of the device motions in seven DOF are compared with numerical predictions for cases where the power take-off was inactive. Initial results indicate close alignment between measured wave-frequency motions and predictions, and provide insights into the device’s hydrodynamic performance in real sea conditions.